Analysis of slope stability to determine the causes of collapse the primary canal in the North-Raman irrigation-area, Central Lampung - Kastamto; Fitri Arniza; Mera Mas; Zain Alfath; Susarman; Dewantoro Fajar (E3S Web of Conferences)
A 25-meter primary-canal in the North-Raman Irrigation-Area (NRIA) collapsed in December 2021. Before the landslide occurred, the rainfall intensity reached 153 mm/hour. Field surveys at the time of the incident revealed that a large enough discharge overflowed from the Raman River, inundating the NRIA. This shows that landslides were most likely triggered by groundwater infiltration due to either high intensity rainfall or flooding. The soil conditions are also unable to support the primary-canal embankment. The present research objective is to carry out slope stability analysis to determine the causes of collapse of the NRIA embankment using the Geo-Slope and Plaxis 8.6 numerical models. Soil parameters are tested and measured in the field and laboratory. The safety factor (SF) at the study site is determined by both models, and then compared with the allowable SF to assess slope stability which should be bigger than 1.5 if no earthquake occurs. However, the Geo-Slope model produces an SF of 0.97. This means that the embankment is very vulnerable to landslides. The laboratory result reinforces this finding where embankment void-ratio is 1.5 (high). A high void ratio can cause water infiltration into the soil, thereby reducing soil stability and bearing capacity.